SOFT SYSTEMS FOR COMMUNITY-BASED HCV MANAGEMENT IN INDONESIAN OIL PALM PLANTATIONS - Indriyana, Neny; Utomo, Suyud Warno; Soesilo, Tri Edhi Budhi; Darmajanti, Linda (Journal of Environmental Science and Sustainable Development, 2026)
Certification mandates under the Roundtable on Sustainable Palm Oil (RSPO) and Indonesian Sustainable Palm Oil (ISPO) have made measurable strides in promoting sustainability standards, yet governance challenges in High Conservation Value (HCV) 4, 5, and 6 management remain insufficiently addressed within Indonesian plantation contexts.  Drawing on adaptive governance theory and the social-ecological systems framework, this study argues that such gaps are structurally linked to the marginalisation of community agency within corporate-dominated decision-making. This study proposes and empirically evaluates an integrated governance framework that positions community engagement as a functional contributor to conservation outcomes within plantation landscapes of West Kalimantan, under conditions where corporate decision-making currently dominates. A concurrent mixed-methods design was applied across three concessions, combining spatial analysis of HCV zones, Management Effectiveness Tracking Tool (METT) assessments across 30 indicators, structured questionnaires administered to 320 community informants, and Soft Systems Methodology (SSM) synthesis into a polycentric management model. Results indicate an overall METT score of 75.8%, revealing pronounced dimensional asymmetries: Output (100%) and Planning (85%) scores substantially exceeded Context and Input dimensions (66.7% each). This reflects the prioritisation of infrastructure over participatory mechanisms with median HCV budget allocations of 2.3% and only 8% community involvement in formal monitoring. A participatory deficit characterised all management phases, as 48% of respondents reported predetermined corporate decisions lacking dialogue, while 71% contested collaborative agreement processes. Despite these limitations, community engagement quality demonstrated a statistically significant positive association with METT performance (r=0.67, p<0.05). Microenterprise activities emerged as enabling conditions for conservation participation. These findings support reorienting HCV governance frameworks to treat community welfare as a primary enabling condition rather than an ancillary co-benefit. The SSM-integrated model establishes a 75% METT threshold as a trigger for adaptive management improvements, offering actionable pathways for reconciling commercial agriculture with biodiversity conservation.